Trauma triptych: inviting cross-disciplinary collaboration in art therapy, social work, and psychiatry. Issue 4 (2nd October 2022) - Corrado, Meagan; Wolf, Denise; Bills, Lyndra
Structured Abstract: Background: Trauma can impact an individual's ability to process memories, develop a healthy identity, express emotions, maintain focus, navigate relationships, and achieve goals. Despite the potential negative impacts of trauma, specific psychotherapeutic interventions and trauma-informed care provide opportunities for recovery and healing. Context: Creative processes can promote trauma recovery. The literature suggests that creativity can support people in non-verbally processing memories, containing internal chaos, and restoring hope. Approaches: Case examples highlight the approaches of an art therapist, social worker, and psychiatrist who introduced arts-based interventions to traumatized clients. The art therapist explores use of an ancient Japanese approach to repairing pottery with a 23-year-old who experienced sexual abuse and neglect. The social worker discusses how Janusian thinking and "creative destruction" inspired collage-making with a 15-year-old who witnessed domestic violence and experienced depressive symptoms. The psychiatrist considers how traumatic memory processing theory informed her structured drawing approach to traumatic grief work with an aggressive 10-year-old. Outcomes: Use of arts-based interventions assisted in overcoming client resistance to "talk therapy" approaches, offering a non-verbal, expressive alternative and supporting client progress toward treatment goals. Implications for Practice: Reflection on three case vignette led to several practice implications: (1) Professionals should use creative approaches carefully and responsibly, operating within their scope of practice, (2) Professionals should consider how arts-based interventions can strengthen trauma treatment, & (3) Increased provider collaboration and cross-disciplinary dialogue can enhance trauma informed care. Implications for Research: More research on the effectiveness of creative approaches in trauma treatment is needed. Plain-language summary: Trauma effects people in many ways. Some people have trouble talking about what happened to them. Others have trouble understanding who they are and where they fit in the world. Trauma makes it hard for people to focus, express themselves, and connect with others. Creativity can help people work through their trauma. Art helps people express themselves when they don't have the words to explain what they have been through. Art helps people feel calmer, stronger, and more hopeful. This article includes three examples of how art helped people work through their trauma. An art therapist talks about how she used broken pottery to help a 23-year-old girl reflect on who she was and where she wanted to go. A social worker talks about how she used paint and ripped pieces of paper to help a 15-year-old girl share her feelings of sadness and hope. A psychiatrist talks about how she helped a 10-year-old boy draw about his mother's death so that he could get his anger under control. The art therapist, the social worker, and the psychiatrist found that helping people use art to deal with trauma was helpful. It gave people a way to express themselves when they didn't feel like talking. It helped people move forward. The information in this article is helpful for other professionals who want to use art in their work with people who have gone through trauma. Art is a powerful tool, and professionals should think carefully about how they use it with people. They should also think about ways that they can work together as they help clients make art and deal with trauma. When professionals work together, they can support each other and learn from one another.